FAKTOR YANG BERPENGARUH DARI PERANCANGAN SISTEM PENDAFTARAN ONLINE PASIEN UMUM DI RUMAH SAKIT KHUSUS BEDAH HASTA HUSADA KEPANJEN - anggryani, femy; Dika Adi Saputro, Mashuri; Santosa, Adi (Malang: Sekolah Tinggi Ilmu Administrasi Malang, 2024)
The development of information and communication technology in the health sector is currently growing rapidly, as evidenced by the existence of an online registration system. The patient registration system at the Hasta Husada Special Surgical Hospital is still done manually, which requires patients to come to the hospital to register and have their data recorded by officers, then the patient waits to be called to be examined based on the queue number, this will take longer and can result in backlogs. patients in four patient registries. The aim of this research was to determine the influencing factors in designing an online general patient registration system basedm on WhatsApp API-gateway using the Wablas Website and WA Queue at the Hasta Husada Special Surgical Hospital. This research uses descriptive analytical research with a qualitative and quantitative approach. The data collection technique used is a questionnaire, then for problem solving using a fishbone diagram, from the problem the author has the idea to solve the problem by creating a WhatsApp-based online registration program with the Wablas Website and WA Queue, using the F test to determine the factors that influence the design of the registration system on line. The subjects in this study were 8 medical records officers in the registration section. The results of research using the Wablas Website and Queue WA applications show that the average scale for respondents is 2.60, where a scale of 2.60 is included in the agree category, so it is stated that respondents showed the highest score of 3.40, the criteria for agreeing in the ease of the patient registration process.It was concluded that the manual registration process for general patients at the Hasta Husada Special Surgical Hospital required the addition of a new registration system that could make things easier for staff and patients. As a consideration for the IT team and medical records officers to design a WhatsApp API-gateway based online registration system using the Wablas Website and WA Queue.